PROFESSIONALISM OF THE PRINCIPAL IN IMPROVING THE PERFORMANCE OF SOCIAL SCIENCE TEACHERS IN THE PRIVATE ELEMENTARY SCHOOL OF NGAWET WEST HALMAHERA - Andriana Katoci Mawea; Jusan Yusuf; Sitirahia Hi Umar; Rustam Hasim; Ramdani Salam; Irwan Abbas (SOSIOEDUKASI, 2026)
This study aims to describe the professionalism of school principals in improving the performance of Social Sciences (IPS) teachers at Ngaweet Private Elementary School, West Halmahera Regency. The professionalism of school principals has an important role in creating a conducive work climate, fostering teacher competence, and encouraging the improvement of the quality of learning. This study uses a qualitative approach with a descriptive method. The research subjects include school principals, social studies teachers, and several related parties in the school environment. Data collection techniques are carried out through interviews, observations, and documentation, while data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the professionalism of school principals is reflected in managerial skills, leadership, academic supervision, and teacher coaching and development. The principal actively provides guidance, motivation, and evaluation of the performance of social studies teachers, so that it has a positive impact on learning planning, the implementation of the teaching and learning process, and the assessment of student learning outcomes. However, there are still several obstacles, such as limited infrastructure and sustainable development of teacher competencies. Therefore, efforts are needed to consistently improve the professionalism of school principals and support from various parties to improve the performance of social studies teachers optimally.